Analisis perbandingan kelembagaan BAZNAS dan BWI dalam pengelolaan instrumen keuangan sosial islam - Auliya, Isnaeni Nur; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2026)
BAZNAS and BWI are official state institutions that play strategic roles in the management of Islamic social finance instruments in Indonesia. However, both institutions have different institutional characteristics, authorities, and operational mechanisms. These differences make a comparative institutional study between BAZNAS and BWI important in understanding the effectiveness of zakat and waqf management in Indonesia. This study aims to analyze and compare the institutional frameworks of BAZNAS and BWI in managing Islamic social finance instruments. The research employs a qualitative method using a library research approach through the analysis of laws and regulations, institutional reports, scientific journals, and other relevant literature. The findings indicate that BAZNAS has an operational role in the direct collection and distribution of zakat funds, while BWI primarily functions as a regulatory institution and supervisor of nazhir in waqf management. In addition, both institutions face similar challenges, such as low public literacy, limited human resources, and the suboptimal digitalization of Islamic social fund management. Therefore, strengthening institutional synergy, regulatory harmonization, and the integration of digital systems are necessary to improve the effectiveness of Islamic social finance management in Indonesia.